Economic Geology, Petrology and Environmental of Copper Ore Deposits of Chagho in South West Karaj (Revista Geoaraguaia, 2021)
The mineral zone under study is 32 square kilometers located in Chagho village, Akhtarabad village, Malard county, Shahriar city, Tehran province. This area is part of the Urumieh-Dokhtar Volcanic Belt. The age of the studied rocks is related to the Eocene and younger than the Eocene. The downward trend of some oxides of major elements such as MgO, CaO and AL2O3 and the increasing trend of K2O and Na2O over SiO2 from the basaltic rocks to the intermediate-acidic rocks in rocks of the studied area are consistent with the magmatic subduction process. Based on standardized radar charts relative to chondrite of the rocks under study, enrichment of elements (LILE) such as Cs, Rb, Ba and light rare earth elements (LREE) relative to HFS elements (Ti, Nb) and heavy rare earth elements (HREE) (Y, Yb, Lu) is shown. In all of the rocks mentioned above, the element u is enriched relative to the primary mantle. The positive anomaly of this element may indicate contamination of their constituent melts with the upper crust. In all studied rocks, HFS elements such as Ti, Nb show depletion and concave pattern. The depletion of the aforementioned elements to the primary mantle may be attributed to the contamination of the melts with lower and upper crustal or possibly the dependence of the melts constituting these rocks on the geodynamic environments of subduction of Neo-Tethyan. According to the study of fluids involved in the region, the temperature of homogenization with the temperature of formation of copper veins is between 120 and 306 ° C, and the salinity percentage varies from 6.45 to 15.96 wt% of sodium chloride. Accordingly, this ore deposit is classified as mesothermal and is a type of hydrothermal allogenic deposits, the presence of sub-faults and seams and gaps in the host rock as a low-pressure environment has provided a suitable site for vein-type mineralization